PERTANGGUNGJAWABAN AHLI WARIS DALAM PEMBAYARAN HUTANG PEWARISSTUDI KASUS PUTUSAN MAHKAMAH AGUNG RI REG.No.180.K/Pdt/1993 - Shafa Salsabila (2022)
In practice, credit agreements are usually carried out with property guarantees charged to the debtor, this aims to avoid things that occur outside the agreement. One of the things that creditors often encounter in agreed credit agreements is that the debtor dies while the credit is still in progress. In this case, the creditor can ask for responsibility for the remaining debt owned by the debtor to the heirs. The purpose of this study was to determine the responsibility of the heirs to the debts of the heirs. The research method used in answering the topic of this problem is normative juridical research or library law research. This research was conducted by using a statutory or statutory approach. The sources of data used in this research are letters, books and documents issued by the government. The results of this study if the heirs receive the inheritance, then all the rights and obligations of the heir during his life also shift to the heirs including the debts. So, based on this, the heirs can be held responsible for the remaining debts of the heirs. However, if the heir does not receive the inheritance, the heirs are not responsible for paying the debt. The debt of the heir cannot be said to be joint debt if one of the parties to the marriage does not know and agree to the existence of the agreement. Keywords: Credit Agreement, Joint Assets, Debt Guarantee, Heirs